SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN KARET MENGGUNAKAN METODE CERTAINTY FACTOR - Zainab, Zainab (STMIK Budi Darma, 2017)
Diseases in rubber plants often cause economic losses in rubber plantations. The resulting losses are not only the loss of yield due to crop damage but also the costs incurred in the control effort. The expert system is a software package or computer programming package intended to provide health and aids in solving problems in certain areas of specialization such as science, engineering, mathematics, agriculture, medicine, and so on. In accordance with the development of information technology, the expertise of rubber plant diseases needs to be implemented into a computer application using expert system method, namely: Certainty Factor (CF). The Certainty Factor method will display a selection of symptoms that can be selected by the user, where each choice of symptoms will take the user to the next symptom option until the final result. At the end result, the system will display the user's symptom choices, and the illness suffered.